(untitled) (Journal of International Studies, 2020)
Laws of war provide it with moral equality that distinguishes it from domestic crimes in that in warfare, some restraint should be observed. Disproportionate destruction of life and property are not permitted and civilian life and civilian property must not be subjected to military force. The need that some restraint should be observed during armed conflict has been recognized since the earliest times in many cultures and religions. Modem international law as stipulated by Article 22 of The Hague Regulations and Article 1 of the Additional Protocol 1 the Geneva Conventions restrict the rights of parties to the conflict to their choice of the methods and means of warfare. In warfare, the employment of weapons and methods of warfare that cause superfluous injury and suffering are not permitted. The same principle applies to the environment. The destruction of environment that exceeds the need to achieve military objectives are not permitted - a development that demonstrates the extend in which environmental issues in warfare has grown in importance. The laws of war also require that civilians and civilian objects be distinguished from the military and be protected from harm. Parties to the conflict are severally responsible to ensure that this rule is observed. In determining the extent of damage and destruction allowed in war, the principle of proportionality should be applied. The main difficulty however lies in how proportionality is interpreted by parties to the conflict.